2011
DOI: 10.1007/s11947-011-0545-3
|View full text |Cite
|
Sign up to set email alerts
|

Technological Aspects of β-Carotene Production

Abstract: β-carotene is the main source of pro-vitamin A and is widely used as a food colorant, with a global market estimated to surpass USD 280 million in 2015. The majority of the β-carotene commercialized in the world is obtained by chemical synthesis from β-ionone. Alternatively, the production of β-carotene can be reached on a biotechnological basis, using filamentous fungi, bacteria, microalgae, and yeasts as producers, or even by extraction from vegetable sources, such as oil palm (Elaeis guineensis) and buriti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 66 publications
0
83
0
6
Order By: Relevance
“…The search for natural sources of β-carotene is of great interest, since only 2% of all commercial β-carotene is naturally produced worldwide (Dufossé et al, 2005;Ribeiro et al, 2011). Carotenoids attracted attention because a number of epidemiological studies have revealed that an (Stahl and Sies, 2003;Mayne, 1996).…”
Section: Total Carotenoidmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for natural sources of β-carotene is of great interest, since only 2% of all commercial β-carotene is naturally produced worldwide (Dufossé et al, 2005;Ribeiro et al, 2011). Carotenoids attracted attention because a number of epidemiological studies have revealed that an (Stahl and Sies, 2003;Mayne, 1996).…”
Section: Total Carotenoidmentioning
confidence: 99%
“…The results indicate that this oil is one of the richest known sources of biological active β-carotene (781. 6 mg·kg −1 ), which imparts the characteristic orange-red color and also lends oxidative protection to the oil (Ribeiro et al, 2011;Benadé, 2013). In the literature, the total carotenoid content of Buriti oil fluctuates between 600 mg·kg −1 to 10,000 mg·kg −1…”
Section: Total Carotenoidmentioning
confidence: 99%
“…9 The accumulation capacity of β-carotene in Dunaliella is influenced by stress factors in culture, such as high light intensity and salt concentration, low temperatures and/or nitrate deficiency. 10 Studies reported in the literature aimed at increasing the production of carotenoids in Dunaliella showed that its concentration varies in a range between 4 and 38 µg mL -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudos demonstram que a composição do meio empregado pode interferir na bioprodução desses pigmentos, além disso, outras condições externas do cultivo como temperatura, agitação, aeração e pH também levam a alterações como variedade e quantidade de carotenoides produzidos pelo micro-organismo (RIBEIRO, et al, 2011;SCHWARTZ, 2010).…”
Section: Introductionunclassified